Coupling of Anaerobic Digestion and Struvite Precipitation in the Same Reactor: Effect of Zeolite and Bischofite as Mg2+ Source - Palominos, N.; Castillo, A.; Guerrero, L.; Borja, R.; Huiliñir, C. (Frontiers in Environmental Science, 2021)
The aim of this research was to assess the simultaneous effect of zeolite and bischofite on estruvite production in an anaerobic digester treating pig slurry as substrate. Three ratios (5:1, 6:1 and 7:1) of Mg-P were used for evaluating the effect of only bischofite on anaerobic digestion. For assessing the simultaneous effect of zeolite and bischofite on anaerobic digestion, three mass ratios of zeolite:bischofite (1, 5 and 10%) were used. As results, bischofite as Mg+2 source served to decrease the total phosphorous (TP) concentration in the anaerobic digestion of pig manure without affecting the maximum methane production rate or methane yield of the system. An average 82.5% TP removal was found in the reactors with bischofite during the first 5 days of digestion. Nevertheless, bischofite increased the lag-phase of the system. The simultaneous presence of zeolite and bischofite (1% ratio with respect to bischofite) caused a TP removal of 65.6% and increased the methane yield by up to 19.9% compared to a system without zeolite or bischofite. Thus, it is feasible to use bischofite and zeolite as enhancers for the simultaneous production of biogas and struvite inside an anaerobic digester treating piggery wastewater.